Loss avoidance during social interactions - Benjamin J. Kuper-Smith; Christoph W. Korn (Communications Psychology)
Abstract Social interactions lead to outcomes for oneself and others, which can be gains or losses. Yet, it is unclear how exactly people’s social decisions are affected by whether an outcome is above or below zero. We systematically varied whether the outcomes of social dilemmas (Prisoner’s Dilemma, Stag Hunt, Chicken) were gains, losses, or combinations thereof. Across seven experiments (4 preregistered; NOffline = 197, NOnline = 1653), participants tried to avoid losses altogether (loss avoidance), but there was no consistent evidence that they tried to minimize losses (loss aversion). If cooperation avoided losses, people cooperated more; if defection avoided losses, people defected more, even if this imposed a loss on the other person. Our results suggest that cooperation and social interactions can be influenced systematically if the situation allows people to avoid losses.